Legal Liability of Notaries for Misuse of Certificate Custody by Third Parties: Case Analysis of Albert Riwukore - Klenten, Bred; Djaja, Benny; Sudirman, Maman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
A notary, as a public official, holds legal responsibility for any document or item entrusted to them in the scope of their professional duties. This paper examines the legal liability of Notary Albert Riwukore regarding the loss of nine land ownership certificates (SHM) that were initially deposited during the credit collateral process between Rachmat (debtor) and BPR Christa Jaya Perdana (creditor). Although the SHMs were retrieved by Rachmat—its legal owner—for photocopying purposes, the retrieval lacked written consent and official documentation from the notary's office. This raised legal concerns under both civil law (tort and breach of contract) and criminal law (alleged embezzlement). The analysis reveals that the notary’s responsibility must be distinguished between administrative negligence and criminal intent. No evidence supports the presence of dolus (malicious intent), although culpa (negligence) may still be applicable. Moreover, Rachmat's voluntary action as the rightful owner to retrieve the certificates eliminates a key element of embezzlement. This study underlines the importance of meticulous documentation systems and precautionary procedures in the notarial profession to avoid potential criminalization of their official duties.